Differences in checkpoint-inhibitor-induced hypophysitis: mono- versus combination therapy induced hypophysitis - van der Leij, Stephanie; Suijkerbuijk, Karijn P.M.; van den Broek, Medard F.M.; Valk, Gerlof D.; Dankbaar, Jan Willem; van Santen, Hanneke M. (Frontiers in Endocrinology, 2024)
Objective: Immune checkpoint inhibitors (ICIs) are revolutionary in oncology but may cause immune-related (IR) side effects, such as hypophysitis. Treatment with anti-PD-(L)1, anti-CTLA-4 or anti-CLTA-4/PD-1 may induce hypophysitis, but little is known about the differences in clinical presentation or need for different treatment. We analyzed the differences of anti-PD-(L)1, anti-CTLA-4 and anti-CTLA-4/PD-1 induced hypophysitis Methods: retrospective analysis of 67 patients (27 anti-PD-(L)1, 6 anti-CLTA-4 and 34 anti-CTLA-4/PD-1 induced hypophysitis). The median time between starting ICIs and IR-hypophysitis was longer after anti-PD(L)-1) therapy (22 weeks versus 11 and 14 weeks after anti-CTLA-4 and anti-CTLA-4/PD-1 therapy, respectively). The majority of patients (>90%), presented with atypical complaints such as fatigue, nausea, and muscle complaints. Headache, TSH or LH/FSH deficiency were more common in anti-CTLA-4 and anti-CLTA-4/PD-1 versus anti-PD-(L)1 induced hypophysitis (83% and 58% versus 8%, 67% and 41% versus 11%, and 83% and 48% versus 7%, respectively). Pituitary abnormalities on MRI (hypophysitis or secondary empty sella syndrome) were only seen in patients receiving anti-CTLA-4 or anti-CTLA-4/PD-1 therapy. Recovery from TSH, LH/FSH and ACTH deficiency was described in 92%, 70% and 0% of patients after a mean period of 14 and 104 days, respectively, and did not differ between patients who did or did not receive high-dose steroids.The clinical presentation of IR-hypophysitis varies depending on the type of ICIs. MRI abnormalities were only seen in anti-CTLA-4 or anti-CTLA-4/PD-1 induced hypophysitis. Endocrine recovery is seen for LH/FSH and TSH deficiency but not for ACTH deficiency, irrespective of the corticosteroid dose.